Acute intermittent porphyria mimicking Guillain-Barré syndrome - Otoya-Durand, Enrique (2023)
A 24-year-old woman was admitted with seizures and severe hyponatremia associated with episodes of tachycardia and sustained arterial hypertension. During her hospitalization she presented muscle weakness and altered sensibility of upper limbs, progressing to all extremities with signs of acute denervation by electromyography. With suspicion of Guilláin-Barré syndrome, therapy with intravenous immunoglobulin was started. A history of previous episodes with recurrent abdominal pain, associated with the current picture of hypertension, tachycardia and seizures led us to consider acute intermittent porphyria as a differential diagnosis. The elevated values of delta amino levulinic acid in blood and porphobilinogen in urine confirmed the diagnosis. The patient presentedwith acute respiratory failure requiring assisted mechanical ventilation in the intensive care unit. She received intravenous hemin late due to lack of availability in the country. She was discharged with tracheostomy and severe sequelae quadriparesis.